Factorizing trinomials
 x2 – 2x – 15 =factorize completely(x + 5)(x + 3)(x – 5)(x + 3)(x – 5)(x – 3)(x + 5)(x – 3) x2 + 13x + 30 =factorize completely(x + 3)(x + 10)(x – 3)(x + 10)(x – 3)(x – 10)(x + 3)(x – 10) x2 – 7x + 12=factorize completely(x + 4)(x + 3)(x – 4)(x + 3)(x – 4)(x – 3)(x + 4)(x – 3) x2 + x – 20 =factorize completely(x + 5)(x + 4)(x – 5)(x + 4)(x – 5)(x – 4)(x + 5)(x – 4) x2 +4 x – 12 =factorize completely(x + 2)(x + 6)(x – 3)(x + 4)(x – 6)(x – 2)(x + 6)(x – 2)  x2 +  11x – 12 =factorize completely( x – 3)(x + 4)( x – 1)(x + 12) ( x + 3)(x – 4)( x + 4)(x – 3)  x2 +  3x - 10 =factorize completely( x +5 )(x - 2)( x -5 )(x + 2)( x -5 )(x - 2)( x +10 )(x - 1)  𝑥2 + 13𝑥 + 42 =factorize completely( x – 2)(x + 21)( x – 3)(x + 14) ( x + 7)(x + 6)( x + 7)(x – 6)  𝑥2 − 5xy − 24 y2=factorize completely(x – 8y)( x + 3y)(x – 6y)( x - 4y)(x + 8y)(2x + 3y)(x + 8y)( x - 3y)  y2 -   y  - 12 =factorize completely( y - 2)(y + 6)( y + 3)(y + 4)( y - 3)(y - 4)( y + 3)(y  - 4)
Students who took this test also took :

Created with That Quiz — where test making and test taking are made easy for math and other subject areas.